Carbonatação da camada de cobrimento de protótipos de concreto com cinza volante e cal - Lana, Elinor Fernando Dalla (2005)
When the armed concrete of the point of view of the durability is observed, observes heterogeneous zone from mold, known as cover concrete that possess distinct characteristics of the zones deepest of the structural parts. It is through the same one that the transport mechanisms act that allow the interaction with the environment through the fluid flow that stream for the pores. Between the properties, that more are affected to leave of this layer, it is the carbonation, mainly when one uses high texts of mineral additions, especially pozzolans, that consume the calcium hydroxide of the alkaline reserve and speed up the neutralization process. When the carbonated depth reaches the armor, this suffers process from depassivation for the fall of pH and is available for the beginning of the corrosion, case the ambient conditions will be propitious. The pozzolans, in special the fly ash, beyond the ecological advantages that its job in concrete brings, produce significant alterations in the improvement of the microstructure of the folder but, on the other hand, it consumes great part of CH, speeding up the carbonation process. The present inquiry deals with the study of cured archetypes of concrete in ambient conditions, of where had been extracted certifications from the surface of the concrete and, after, the 2,5 and 5,0 cm of depth, with intention to study the influence of the distance to the external surface on the process of carbonatação, pH and CH. Mixtures with cement Portland (reference) and its substitution had been used, in mass, for 50% of fly ash, with and without addition of hydrated lime. Climatized chamber was used to carry through the assays of sped up carbonation, determining the depths neutralized in 4, 8 and 12 weeks. To leave of these data the carbonatação coefficients had been calculated, of where it can be concluded that the cement substitution for 50% of fly ash increased, in average, in 100% the speed of the carbonation, while that the addition of 20% of lime to these traces made with that increase it to me average lowered for 20%, in average. Also it can be concluded that layer 3, 50 mm of the surface, was the one that more was benefited with the addition of lime in relation to the reference concrete therefore presented coefficient of carbonation of only 40% greater, content of higher CH 5.8%, agreed water content 4% greater and, finally, text of 10 lesser pores of nm raised 10.6% more.